Molecular epidemiology of carbapenemase-producing multidrug-resistant gram-negative bacilli isolated from different infection sites (Research, Society and Development, 2021)
Resistance to carbapenemases in gram-negative bacilli (BGN) has become a worldwide problem, increasing the rate of morbidity and mortality. The automated method was used for identification and susceptibility of isolates. And the molecular method was applied in the detection of gram-negative bacilli (BGN) producing carbapenemase. A total of 205 BGN were recovered from different carbapenemase-resistant clinical specimens. Resistance genes blaKPC (57,5%), blaVIM (30,2%), blaGES (17%), blaNDM (15%) and blaSPM (2,4%) were recovered from clinical isolates. The blaIMP gene was not detected in any of the isolates. It is worrying that Pseudomonas aeruginosa and Acinetobacter baumannii represent the majority of isolates (61.6%) recovered from infections at different sites, with high resistance to carbapenems, carrying simultaneously the blaKPC, blaGES and blaVIM genes, as well as found in Enterobactericeae. The most prevalent carbapenemase was blaKPC and blaVIM, followed by blaNDM among the resistant multidrug isolates. These results are a threat to public health, configuring high rates of resistance, limiting therapeutic options.